2011
DOI: 10.1188/11.onf.e72-e80
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Clinical Research Nursing Domain of Practice

Abstract: Purpose/Objectives To develop and validate a taxonomy for the domain of clinical research nursing. Design Survey. Setting Clinical research settings in the United States. Sample A purposefully selected expert panel of 22 nurses who were actively practicing or supervising in a clinical research environment. Methods A study team consisting of nurses with experience in clinical research synthesized peer-reviewed articles, academic curricula, professional guidelines, position descriptions, and expert opini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 19 publications
0
49
0
6
Order By: Relevance
“…Other nurses are employed by investigators or clinical research companies and are charged with coordinating single or multiple clinical research protocols. Castro et al (2011) defined clinical research nursing practice as having "a focus on the care of clinical research participants and management of a clinical research protocol" (p. 8). Research nurse coordinators manage the operation of an average of six protocols and the care of 80 or more study patients annually (Getz, 2013;Getz, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other nurses are employed by investigators or clinical research companies and are charged with coordinating single or multiple clinical research protocols. Castro et al (2011) defined clinical research nursing practice as having "a focus on the care of clinical research participants and management of a clinical research protocol" (p. 8). Research nurse coordinators manage the operation of an average of six protocols and the care of 80 or more study patients annually (Getz, 2013;Getz, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An expert committee of clinical research nurses identified and validated five dimensions that constitute the domain of clinical research nursing practice: (a) clinical practice, (b) care coordination and continuity, (c) study management, (d) human subject protection, and (e) contributing to the science (CRN2010 Clinical Research Nurse Domain of Practice Committee, 2009). Castro et al (2011) conducted a study to describe the specific role activities performed in each of these five domains. Bevans et al (2011) further differentiated the role activities of nurses working as clinical research nurses, clinical research coordinators (CRCs), and nurse practitioners in clinical research settings.…”
Section: Introductionmentioning
confidence: 99%
“…The cornerstone of CRN is the provision and coordination of nursing care for participants in clinical research studies (1). A strategic plan and team structure engaging all leadership in nursing and nursing shared governance, called Clinical Research Nursing 2010 (CRN 2010 ), was established, and groups worked for 4 years to create and validate concept documents, communicate through nursing management and advanced practice nursing structures, and discuss them with staff shared governance (SG) leaders (2). Nursing leadership then turned from the application of the specialty of CRN to the process of planning, delivering, coordinating and evaluating care provided to research participants in the CC.…”
mentioning
confidence: 99%
“…[15][16][17] The American Nurses Association (ANA) and the International Association of Clinical Research Nurses have copublished Scopes and Standards of Clinical Research Nurses. 18 ANA formally recognized clinical research nursing as a professional nursing specialty.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Comparative research that demonstrates the RN-CRC contributions (e.g., quality indicators) to informed consenting, eligibility, safety, and endpoint assessment is lacking. 16 Moreover, as the complexity of patient populations, clinical research studies and assessments increase, the requirements for hiring RN-CRCs should be increasing, rather than decreasing. To bridge the gap in research, this pilot study compares quality and safety variables based on the frequency of protocol deviations by RN-CRCs to unlicensed CRCs.…”
Section: Introductionmentioning
confidence: 99%